Peningkatan Kinerja Manajerial berbasis Anggaran Partisipasi - Aprih Santoso; Andre Setyo Nugroho; M. Hasan Ma'ruf (Politeknik Ganesha Medan, 2022)
This study examines the effect of budgetary participation and perception of innovation on managerial performance and tests whether perception of innovation mediates the effect of budgetary participation on managerial performance in public sector organizations. The study was conducted at the Semarang City Health Office and Semarang City Health Centers, with 60 respondents from echelon officials, using the path analysis method. The results of the analysis show there is a direct influence between budgetary participation and the perception of innovation on managerial performance and the perception of innovation not being able to mediate the relationship between budgetary participation on managerial performance in the Semarang City Health Service and Puskesmas throughout the City of Semarang